WITH IMPROVED BLADE MIXER RESULTS OF RESEARCH WORK ON THE DEVELOPMENT OF THE 5LP LINTER - Nomanov, Mirjalal (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Prpeller ends seed roller rotation towards 60 degrees bent and bent 16 mm long mixer, Namangan region Related to "Namangan Pakhta TEKS" LLC Kosonsoy cotton cleaning to the 5LP linter in the enterprise installed and linter improved. Improved in order to study the effectiveness of the linter, a comparison-research work was carried out with a 5LP linter with an existing mixer in the Andijon-36 selected cotton grade I and III technical seed at a distance of 9-12 mm with the mixer blades selected on the basis of theoretical and practical research. In the comparative work, the fluffiness of the seed after the linter was 6.85-8.24% on average, and the damage was on average 5.42-4.25%. showed an average of 0.34 (abs)% to 0.27 (abs)% less than seed hairiness and an average of 0.36 (abs)% to 0.4 (abs)% less than damaged seed. The mass fraction of impurities and whole seeds in the lint produced changed from an average of 5.96 % to 5.38 %, compared to the mass fraction of impurities and whole seeds in the fluff produced from the existing 5LP linters from 0.51 (abs)% to 0.77 (abs ) decreased by %. The staple length of the fluff is 6/7 mm, and due to the improvement of its quality, according to the state standard UzDst 645:2016, it corresponded to the I type B type "Middle" class. In this case, the productivity of the linter changed from 693 kg/h to 745 kg/h for seed, and from 27.9 kg /h to 24.8 kg /h for fluff, compared to the productivity of the existing 5LP linter taken for the experiment by 70 kg /h . It was found to be higher than 2.5 kg /h to 3.1 kg/h for fluff at 34 kg /h .